INTERNATIONALISATION OF SMALL AND MEDIUM-SIZED ENTERPRISES IN THE EU-28 (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
International trade activities of the European Union Member States do not only influence the world trade but also make a substantial contribution to the European economy. Free trade between the European Union Member States is one of the EU's founding principles. Small and medium-sized enterprises, engaged in cross-border activities, do not only develop new business opportunities, but become more innovative, productive, and hence grow faster. The purpose of this paper is to provide a better grasp of the internationalisation of SMEs and its benefits within the current globalised world trade. Using newly gathered data from the Eurostat and World Bank, this paper outlines the main features of a broad range of data on international trade focusing on the SMEs actively engaged in importing and exporting within and outside the EU. Analyses show that despite the significant direct and indirect benefits internationalisation can have for small and medium-sized enterprises, the majority of SMEs are not engaged in international trade. Although, overall, SMEs make a substantial contribution to European Union exports and imports, there is still a huge share of SMEs which are not involved in international activities at all due to a consistent set of obstacles and barriers. Although, large enterprises contribute with only a small share of the number of importing and exporting enterprises for both intra and extra EU trade in goods, still many Member States account for the largest share in trade value among the four size classes.